2022
DOI: 10.3390/agronomy12102550
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gypsum and Bio-Priming of Maize Grains on Soil Properties, Physiological Attributes and Yield under Saline–Sodic Soil Conditions

Abstract: In order to enhance soil qualities and boost crop output, gypsum, plant-growth-promoting rhizobacteria (PGPR), and chitosan are all viable solutions. This study’s goal was to find out how different amounts of chitosan—0, 25, 50, 75, and 100 mg L−1—in combination with gypsum and PGPR inoculation (Azospirillum lipoferum + Bacillus subtilis), affected the yield of maize plants growing in saline–sodic soil. Field tests were carried out in triplicate across two growing seasons, 2020 and 2021, using a split plot des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…95,96 Studies have shown the positive correlation between the biopriming and activities of soil enzymes, including urease, dehydrogenase, cellulase, alkaline phosphatase and invertase. 97,98 Furthermore, the combination of biopriming and gypsum amendment significantly enhanced the bulk density, electrical conductivity and proportion of exchangeable sodium of salinesodic soil. 98 Seeds bioprimed with T. asperellum combined with inorganic fertilizer amendment showed a significant improvement in soil cation exchange capacity and nutrient (i.e.…”
Section: Effect Of Biopriming On Soil Nutritional Status and Fertilitymentioning
confidence: 99%
See 2 more Smart Citations
“…95,96 Studies have shown the positive correlation between the biopriming and activities of soil enzymes, including urease, dehydrogenase, cellulase, alkaline phosphatase and invertase. 97,98 Furthermore, the combination of biopriming and gypsum amendment significantly enhanced the bulk density, electrical conductivity and proportion of exchangeable sodium of salinesodic soil. 98 Seeds bioprimed with T. asperellum combined with inorganic fertilizer amendment showed a significant improvement in soil cation exchange capacity and nutrient (i.e.…”
Section: Effect Of Biopriming On Soil Nutritional Status and Fertilitymentioning
confidence: 99%
“…97,98 Furthermore, the combination of biopriming and gypsum amendment significantly enhanced the bulk density, electrical conductivity and proportion of exchangeable sodium of salinesodic soil. 98 Seeds bioprimed with T. asperellum combined with inorganic fertilizer amendment showed a significant improvement in soil cation exchange capacity and nutrient (i.e. nitrogen, phosphorus and potassium) status of the soil.…”
Section: Effect Of Biopriming On Soil Nutritional Status and Fertilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Biochar addition to the soil increases its pH and improves nutrient availability and uptake by plants 17 . For example, biochar increases the availability of fixed phosphorous with high contents of aluminum (Al 3+ ) and iron (Fe 2+ ) under acidic conditions 18 , and improves the bioavailability of nitrogen (N), phosphorous (P), potassium (K), Ca 2+ , and Mg 2+ 19 . Different feedstocks have been examined for biochar production to improve soil properties, including wood-biomass, agricultural crop residues (rice straw and husk, wheat straw) as well as grasses 20 .…”
Section: Introductionmentioning
confidence: 99%
“…[13]. Several studies showed that application of bio-fertilizers in combination with chemical ones improved growth and yield of the crops [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%